The Effect of Counseling on Self-Esteem and Health-promoting Behaviors in Psychiatric Patients Receiving Electroconvulsive Therapy: A Clinical Trial Study - Parisa Rostami; Efat Sadeghian; Ali Akbari (Hamadan University of Medical Sciences, 2021)
Background and Objective: Compared to the general population, patients with psychiatric disorders, especially patients receiving electroconvulsive therapy due to its nature, and lack of psychiatric nursing counseling have worse physical health and lower self-esteem. The aim of this study was to determine the effect of psychiatric nursing counseling on self-esteem and health-promoting behaviors of patients receiving electroconvulsive therapy in hospitalized patients. Material and Methods: This clinical trial was conducted on 114 patients undergoing ECT at Farshchian Hospital in Hamadan, Iran, in 2019. The participants were divided into two groups of intervention (n=57) and control (n=57) by block randomization. Data collection tools included demographic, Rosenberg self-esteem, and health-promoting behaviors questionnaires. The intervention in the experimental group was held in the form of 4 sessions of individual counseling. Data were analyzed using frequency, percentage, mean and standard deviation statistics, Chi-square and t-tests in SPSS software version 20. Results: The mean (standard deviation) of self-esteem score before the intervention in the experimental group (4.01) 21.60 and control (3.51) 21.95 was not significantly different (P=0.542). But the mean score of self-esteem immediately after the intervention in the experimental group (25.47. 3.91) and in the control group (2.79) was 19.11 and two weeks after the intervention, which was significant (P<0.001). The mean and standard deviation of the health-promoting behaviors before intervention in the control group 96.67 (6.028) and intervention group 92.44 (5.444) were statistically significant (P<0.05). Also, this difference was significant between the intervention group (51.539) 91.30 and the control group (5.976) 83.12 immediately and two weeks after the intervention (P<0.001). Conclusion: Psychiatric counseling increased self-esteem and prevented a decline in health-promoting behaviors. Therefore, this method can be used in educational programs and nursing care for patients with mental disorders.